Optimalisasi Usaha Ternak Ayam Petelur dengan Teknologi Pakan Probiotik di Kelompok Peternak Kabupaten Blitar - Panji Purnomo; David Kurniawan; Rosidi Azis (Jurnal SOLMA, 2026)
Background: The Mitra Karya Farmer Group in Slorok Village, Doko District, Blitar Regency faces a major challenge: low business efficiency due to high feed costs and reliance on commercial feed. This community service activity aimed to improve farmers’ knowledge and skills in optimizing layer chicken farming by implementing probiotic feed technology. Method: The program was carried out using a Participatory Action Research (PAR) approach involving lecturers and students from AKN Putra Sang Fajar Blitar, as well as farmers, as active partners. The implementation method consisted of several stages, including observation and problem identification; a pre-test to determine farmers’ initial knowledge; technical training and mentoring on the production of herbal probiotics using local materials; feed formulation and the application of probiotic feed; and evaluation through a post-test and monitoring of technology adoption. Results: The results showed a significant increase in farmers’ understanding, as indicated by the average score rising from 5.2 on the pre-test to 8.7 on the post-test, representing a 67.3% increase. In addition, farmers were able to independently produce and apply probiotics in feed, which has the potential to improve feed efficiency and stabilize egg production. This activity contributed to strengthening farmers’ technical capacity and encouraging the adoption of feed technology innovations based on local resources. Conclusion: Ongoing assistance is needed to ensure that the implementation of probiotic technology yields optimal impacts on productivity and the sustainability of layer chicken farming.